If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3a + 2) = 0 Reorder the terms: 5(2 + 3a) = 0 (2 * 5 + 3a * 5) = 0 (10 + 15a) = 0 Solving 10 + 15a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 15a = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 15a = 0 + -10 15a = 0 + -10 Combine like terms: 0 + -10 = -10 15a = -10 Divide each side by '15'. a = -0.6666666667 Simplifying a = -0.6666666667
| -4.4(12x+20)+10=20x-2 | | -4.5(12x+20)+10=20x-2 | | -5(12x+20)+10=20x-2 | | -6(12x+20)+10=20x-2 | | -4(12x+20)+10=20x-2 | | -2(12x+97)+10=20x-2 | | -2(12x+98)+10=20x-2 | | -2x^2-6x+1=0 | | -2(12x+98)10=20x-2 | | 9x^4-x^2-9x^2y^2+y^2=0 | | -2(12x+38)+10=20x-2 | | -2(12x+28)+10=20x-2 | | -2(12x+27.5)+10=20x-2 | | -2(12x+26.5)+10=20x-2 | | x*1.4=12 | | -2(12x+26)+10=20x-2 | | -2(12x+27)+10=20x-2 | | -2(12x+17)+10=20x-2 | | -2(12x+6)+10=20x-2 | | -2(12x+6)+10=10x-2 | | -2(12x+6)+17=10x-2 | | -2(4x+6)+17=10x-2 | | -3(4x+6)+17=10x-2 | | 0.03/12 | | 3(4x+6)+17=10x-2 | | 3(-4x+6)+17=10x-2 | | 3(-4x+6)+17=5x-2 | | 3k-K= | | 16+3y=31-2y | | r=6k-s | | 10b+3=20 | | 4(a-5)-3(2a+1)=8(a+2)+3 |